Concurrent heavy use of general and oral health services among Finnish adults - Salusjärvi-Juopperi Helena; Tolvanen Mimmi; Linden Jari K; Nihtilä Annamari; Lahti Satu (Stephen Hancocks Ltd. in association with Dennis Barber, 2022)
The aim was to identify heavy users of public health (PHS) and public oral health (POHS) services and combined and concurrent users of these services.\nNumbers of 18+ year-old patients and their visits to POHS (12,124 patients) and PHS (28,479 patients) were collected from two patient registers in a Finnish town in 2013. The combined dataset consists of 32,481 patients. Using a highest decile criterion for both for POHS and PHS, those patients who had made 8 or more visits were categorised as heavy users. Patients who had made total of 10 or more visits to the POHS and/or PHS were categorised as combined heavy users. Patients who had made 8 or more visits to both the POHS and PHS were categorised as concurrent heavy users (195 patients).\nHeavy users of POHS were more often men and those of PHS more often women. Combined heavy users were likely to be women and to be older. The combined heavy users accounted for 40% of all visits of POHS and/or PHS. Among them 30% did not have any POHS visits and 4% did not have any PHS visits. Concurrent heavy use was rare, involving 0.06% of all patients, but made 3.4% of all visits.\nOf the patients making 10 or more POHS and/or PHS visits, only five percent were concurrent heavy users of both services. As many non-communicable diseases share common risk factors the combined heavy users of PHS should be directed to use POHS and vice versa.